Design of small horizontal axis wind turbine for low wind speed rural applications. (2020) - Suresh, A.; Rajakumar, S.
Abstract: In this study, a 2 kW small scale horizontal axis wind turbine with rotor radius of 1.8 m and Tip Speed Ratio of 6 was designed to work at low wind speed for rural applications. Aerodynamic analysis was performed on 10 airfoils, viz Aquila, BW-3, E387, FX63-137, NACA0012, NASA LS-0413, RG-15, S1223, SD7080 and SG6043 using QBlade software. These airfoils were used to analyze Lift Coefficient, Lift to Drag ratio, with different angles of attack and compared with one another. From Numerical simulation, SD7080 was the most suitable airfoil to start producing high power in low wind speed applications.